Pengaruh Media Pembelajaran DUPAN (Dadu Pancasila) terhadap Kemandirian dan Motivasi Belajar Siswa di UPTD SDN Tunjung 4 Burneh Bangkalan - Wijaya, Shepty; Yunita Hariyani; Zainal Arifin (Penerbit STKIP PGRI Bangkalan, 2023)
This study aims to determine the effect of Dadu Pancasila learning media (DUPAN) on learning independence and student motivation at UPTD SDN Tunjung 4 Burneh Bangkalan with this quantitative research using a pre-experimental design type one group pretest-posttest. The sample is class III students of SDN Tunjung 4 Burneh Bangkalan, as many as 36 students. The instrument used non-test is a questionnaire of independence and learning motivation. While the analysis tests are validity test, reliability test, normality test and paired sample t-test with the help of the IBM SPSS v21.0 application. This is evidenced in the use of Google site media in learning Islamic religious education to increase motivation and student learning outcomes obtained a significant value (2-tailed) of 0.000 <0.05, which is a difference in learning independence and learning motivation in the use of learning media (DUPAN) Pancasila dice to increase student independence and motivation.